Codeposition of Nanocrystalline Co-Ni Catalyst Based on 1-ethyl-3-methylimidazolium Bisulfate and Ethylene Glycol System for Hydrogen Evolution Reaction. Issue 16 (1st January 2019) - He, Xinkuai; Sun, Zhengyang; Zou, Qingtian; Yang, Jingjing; Wu, Luye
Abstract : The codeposition behavior of Co(II) and Ni(II) in 1-ethyl-3-methylimidazolium bisulfate ([EMIM]HSO4 ) ionic liquid (IL) and ethylene glycol (EG) system is recorded using cyclic voltammetry (CV). The result indicates that the mechanism of Co-Ni codeposition is an anomalous codeposition, and both the inhibition for Ni(II) reduction and the anomalous codeposition phenomena can be improved by the increase of Co(II) concentration in the system. These Co-Ni deposits are characterized using EDS, XRD and SEM. SEM micrographs indicate that the surface morphology of Co-Ni deposits can be changed by the increase of Co content, and these deposits with many additional elongated acerose crystals, which are germinated on the spherical "nodules" surface, can be prepared. XRD pattern reveals the feature peak of crystalline Co1.2 Ni2.8  with a preferred orientation direction and the average size of grains is calculated to be about 14.6 nm. Moreover, the electrocatalytic activity for hydrogen evolution reaction (HER) on the prepared Co-Ni catalyst surface is investigated using linear sweep voltammetry (LSV) and electrochemical impedance spectra (EIS). These results indicate that the obtained catalyst presents an excellent electrocatalytic activity and durability for HER with an overpotential of 139 mV at 10 mA cm −2 in 1 M KOH solution.